Institutional Pressure and Circular Economy Performance: Collaborative Circular Supply Chain Capabilities in Indonesia’s Fertilizer Industry - Primantara, Ari; Fahmi, Muhammad Ainul; Rozudin, Maghfur; Ardianto, Rizal (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractThe global environmental crisis and the fertilizer industry’s dependence on phosphate and gas are accelerating the shift toward a circular economy. This transition requires more effective management of nutrient flows, waste, and cross-actor collaboration along integrated supply chains. This study examined how external pressures influence environmental sustainability commitments and how alliance, engagement, and circular supply chain capabilities shape circular economy performance in Indonesian fertilizer companies. A quantitative approach was applied through a cross-sectional survey of 122 companies and analysis using Partial Least Squares Structural Equation Modeling. The results show that external pressures strengthen environmental sustainability commitments (path coefficient = 0.658), and that commitment enhances alliance capabilities (0.782) and engagement capabilities (0.737). Alliance capabilities and engagement capabilities jointly explain the development of circular supply chain capabilities (R² = 0.826). Circular supply chain capabilities are the strongest predictor of circular economy performance (path coefficient = 0.769; R² = 0.892), indicating a stable and significant causal structure. These findings confirm that the success of a circular economy in the fertilizer industry depends on companies' ability to translate institutional pressures into strategic commitments and collaborative capability bundles that support reverse logistics, residue utilization, and nutrient recovery.Keywords: circular economy, circular supply chain, environmental sustainability commitment, alliance capabilities, fertilizer industry AbstrakKrisis lingkungan global dan ketergantungan industri pupuk pada fosfat dan gas mendorong transformasi menuju ekonomi sirkular. Transisi ini menuntut pengelolaan aliran nutrien, limbah, dan kolaborasi lintas aktor yang lebih efektif di sepanjang rantai pasok industri terintegrasi. Penelitian ini bertujuan menguji pengaruh tekanan eksternal terhadap komitmen keberlanjutan lingkungan dan peran kapabilitas aliansi, kapabilitas keterlibatan, dan kapabilitas rantai pasok sirkular dalam membentuk kinerja ekonomi sirkular perusahaan pupuk di Indonesia. Pendekatan kuantitatif digunakan melalui survei potong lintang terhadap 122 perusahaan pupuk dan analisis Partial Least Squares Structural Equation Modeling. Hasil menunjukkan bahwa tekanan eksternal meningkatkan komitmen keberlanjutan lingkungan dengan koefisien jalur 0,658 dan komitmen tersebut memperkuat kapabilitas aliansi sebesar 0,782 serta kapabilitas keterlibatan sebesar 0,737. Kapabilitas aliansi dan kapabilitas keterlibatan bersama-sama menjelaskan pembentukan kapabilitas rantai pasok sirkular dengan koefisien determinasi 0,826. Kapabilitas rantai pasok sirkular menjadi penentu utama kinerja ekonomi sirkular dengan koefisien jalur 0,769 dan koefisien determinasi 0,892 sehingga struktur hubungan kausal stabil dan signifikan. Temuan ini menegaskan bahwa keberhasilan ekonomi sirkular di industri pupuk bergantung pada kemampuan perusahaan menerjemahkan tekanan institusional menjadi komitmen strategis dan bundel kapabilitas kolaboratif yang mendukung logistik balik, pemanfaatan residu, serta pemulihan nutrien.Kata kunci: ekonomi sirkular, rantai pasok sirkular, komitmen keberlanjutan lingkungan, kapabilitas aliansi, industri pupuk